What we give, we get back: Investigating the dimensions that influence knowledge sharing on profit enterprise in Indonesia. Issue 5 (9th October 2019) - Saide, Saide; Astuti, Endang Siti; Indrajit, Richardus Eko; Trialih, Rahmat; Diniaty, Amirah; Dewi, Fitriyana; Herzavina, Herzavina
Abstract : Purpose: As prior study offered further general context of knowledge management approach while misplaced more personal behavior development in the context of knowledge sharing practices, this study examined whether and why personal factors predict knowledge sharing practices. This study aims to integrate and analyze indicators such as altruism, grant, interaction ability and knowledge sharing participation to develop a comprehensive behavioral model. Design/methodology/approach: Structural equation modeling was used to check the research hypotheses framework with 268 samples of eight profit companies in Indonesia, divided into broadcasting, banking and services company. Findings: The results showed that altruism and interaction ability factors are significantly correlated with knowledge sharing participation. The findings may help companies and workers to initiate knowledge sharing implementation and encourage knowledge sharing in the internal company. Research limitations/implications: The research focused on profit company in a single province in Indonesia. Further research may extend the study with a focus on non-profit organizations (e.g. academic institutions) and different geographical areas. Practical implications: Managerial ideally creates standardization or regulation that to encourage participation of workers for transfer their knowledge. In this aspect, the company needs to organize, such as formal/informal training and meeting to make their workers more confident to communicate with each other. Originality/value: Prior studies explored knowledge sharing behavior in a general sense; this paper examined the phenomenon specifically within the context of broadcasting, banking and services company in Indonesia, then analyzed the potential for a company to enhance their knowledge sharing strategy.